Improving Tax Compliance without Increasing Revenue: Evidence from Population-Wide Randomized Controlled Trials in Papua New Guinea - Christopher Hoy; Luke McKenzie; Mathias Sinning (Institute of Labor Economics (IZA), 2020)
This paper studies the impact of "nudges" on taxpayers with varying tax compliance histories in Papua New Guinea. We present the results from two population-wide randomized controlled trials in a setting that is characterized by low compliance rates and a lack of effective enforcement. We test the impact of text messages, flyers and emails that remind taxpayers of declaration due dates and provide information about the public benefits from paying tax. We find that the treatments increased the number of tax declarations filed without increasing the amount of tax paid because the taxpayers who responded to the nudges were largely exempt from paying tax. This result is consistent across tax types, communication channels and time periods. We also find that the treatments had no impact on previously non-filing taxpayers. Collectively, our results indicate that taxpayers who face the lowest cost from complying are most likely to respond to a nudge.
Keywords: C93; D91; H2; H20; O1; O17; 330; tax compliance; field experiments; behavioral economics